Safety and immunogenicity of inactivated Zika virus vaccine by gamma irradiation - Pumin Sintara; Puttawat Suphaprueksapong; Suwimol Jetawattana; Witthawat Wiriyarat; Yada Akkhawattanangkul; Komgrid Charngkaew; Nusara Chomanee; Jantip Saelee; Artit Wongsa; Thongkoon Priengprom; Boonrat Tassaneetrithep (Vaccine: X)
Developing the Zika virus (ZIKV) vaccine remains a critical global public health need. This study assessed the safety and immunogenicity of gamma-irradiated Thai ZIKV isolate. Inactivation was confirmed by serial passaging and detection of viral replication using RT-PCR, which demonstrated complete loss of infectivity in ZIKV irradiated with 25 and 50 kGy. Western blotting confirmed that irradiation preserved viral envelope protein antigenicity. BALB/c mice were subcutaneously immunized twice with 25 kGy-irradiated ZIKV, either alone or with alum adjuvant, at two-week intervals. No mortality or local reactions were observed in any group of mice. Antigen-specific IgG and neutralizing antibody titers were measured by ELISA and focus reduction neutralization test, respectively. T cell responses were assessed via intracellular IFN-γ and TNF-α staining by flow cytometry. The irradiated vaccine induced ZIKV-specific antibody and cytokine-producing T cell responses; however, neutralizing antibody titers were low. Mice immunized with irradiated ZIKV combined with alum adjuvant had higher ZIKV-specific antibody titers and T cells producing IFN-γ or TNF-α than those without adjuvant, though differences were not statistically significant. Although the viral integrity and antigenicity remained unchanged, these findings demonstrate that gamma-irradiated ZIKV is non-infectious and immunogenic in mice, supporting its safety profile and the potential for further optimization in future dose-ranging and efficacy studies.